The Synergy Between Law And Technology Towards Justice System Reform In Indonesia - Lukas Norman Kbarek; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku; I Dewa Gede Herman Yudiawan (Fakultas Hukum, Universitas Warmadewa, 2023)
This study aimed to examine the Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2022 concerning Electronic Mediation in Courts and analyze the effectiveness of E-Courts and Electronic Mediation efforts in the justice system in Indonesia. This type of research is normative legal research. This research is a descriptive qualitative research that describes the existence and role of E-Court to realize efficiency and effectiveness in the justice system in Indonesia. The writing of this article used secondary legal materials, namely books, journals, articles, and other written works originating from both printed and internet media, as well as phenomena that occur in the field. The results show that the Mediation Procedure in Court in its implementation aims as an alternative step to reconcile civil disputes in Indonesia. In this case the procedural law used is civil procedural law (HIR) and Rbg, as well as technically and operationally used as a reference is the Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2022 concerning Mediation in Courts Electronically